Gazprom: a long march to market-based pricing in Europe? - Stern, J (Oxford Institute for Energy Studies, 2015)
For several decades up to the late 2000s, the netback market pricing formula – which links gas prices (principally) to oil product prices – dominated international gas transactions in Europe. This type of price formation is consistent with charging different prices to different national markets, as well as to different end-use sectors within the same market, depending on: their location, the fuels which compete with gas in their energy markets, and their ability to access alternative gas supplies (which was severely limited prior to the introduction of liberalization and competition). The formula institutionalized the practice of discriminating monopoly pricing – charging the highest possible price just short of a level which would cause customers to switch to other fuels and thereby maximizing the returns from sales to different markets – which was practised by all gas sellers (and European utility companies) prior to the arrival of competition.